Analysis of Economic and Social Factors Against Social Security in West Java - Auza, Tahta Azzera; Suman, Agus (Journal of Development Economic and Social Studies, 2026)
This study aims to analyze the influence of economic and social factors on crime in West Java from 2014 to 2024. The variables used include GRDP per capita, poverty, social assistance spending, population density, and average years of schooling. The study used a quantitative approach with a panel data regression method in 27 districts/cities in West Java. The results show that GRDP per capita and population density have a positive and significant effect on crime. Meanwhile, poverty and social assistance spending have no significant effect. Average years of schooling showed a significant positive effect on crime. All variables simultaneously influence crime with an Adjusted R² value of 72.1%. These findings indicate that crime in West Java is more caused by structural factors such as urbanization, population density, and development inequality than absolute poverty. Therefore, local governments need to encourage more inclusive development, economic equality, urban area planning, and strengthening social policies to maintain social security stability.